Simulation-Based Optimization of Indoor Lighting Systems for Simultaneous Illuminance Compliance and Energy Efficiency in a Higher Education Digital Library - Alex Sandria Jaya Wardhana; Andri Tri Nugroho; Edy Supriyadi; Sukir (DPTE FT UNY, 2026)
Indoor lighting systems must satisfy illuminance standards while maintaining energy efficiency; however, achieving this balance remains challenging in practice. This study evaluates and optimizes lighting performance in a higher education digital library based on SNI 6197:2020. A quantitative framework integrating analytical modeling and DIALux evo simulation is developed. The problem is formulated as a constrained optimization to minimize illuminance deviation under lighting power density (LPD) limits, using field measurements for validation. Initial results show that only 48.3% of rooms meet illuminance standards, while 93.1% operate below allowable LPD limits. Severe under-illumination is observed in critical spaces, with deviations up to −60.3%, despite low LPD values (2.15 - 2.95 W/m²), while some rooms exhibit over-illumination. Statistical analysis indicates a weak and non-significant relationship between LPD and illuminance (Pearson r = 0.239, p = 0.212, R² = 0.057), with a moderate monotonic trend (Spearman ρ = 0.459), confirming that installed power is not a reliable predictor of performance. These findings reveal that increasing installed power does not guarantee compliance. After optimization, all rooms achieve 100% compliance with an average illuminance improvement of 82.5%. These results demonstrate that lighting performance is primarily governed by spatial distribution rather than installed power.